Working precariously within the social welfare system in Japan during the COVID-19 pandemic: Resilience without resistance among non-regular frontline workers. Issue 3 (3rd July 2022) - Ichikawa, Viveka; Niki, Izumi; Sakamoto, Izumi
ABSTRACT: The global COVID-19 pandemic exposed structural inequality perpetuated by neoliberalism. essential workers, including helping professionals, have experienced a high-stress level. This pilot study examined the challenges faced by social welfare workers in Japan during the pandemic. Japanese social welfare departments in municipal governments, which are primary providers of public assistance and social services, are staffed by government officers (GOs, permanent government employees) and non-regular frontline workers (NRs, hired on annual contracts, predominantly female, covering direct casework). Informed by narrative inquiries, five individual interviews of GOs and NRs were conducted. The thematic analysis highlighted the increased employment instability, individualisation, and powerlessness among NRs. NRs expressed intensified stress from the safety risk, long working hours, and insufficient organisational support. Stratified by different types of contracts, resultant tasks, and genders, NRs experienced intensified isolation, leading to burnout. The implications of working precariously in the pandemic under the neoliberal social welfare systems are discussed.